Isolated Acute Rheumatic Pancreatitis: A Case Report - Muthiah, Ramachandran (British Journal of Healthcare and Medical Research, 2024)
Aim: To emphasize the role of antibiotics in acute pancreatitis as prophylactic and therapeutic benefits. Case Report: A 32-year old obese male was admitted with acute abdomen in the emergency room. He was supported with intravenous fluids and the blood chemistry revealed elevated amylase and lipase levels, raised ESR and a positive ASO titer test. CT abdomen suggested interstitial edematous pancreatitis (IEP) and no fluid collection. Patient was treated with IV cefotaxime and metronidaziole and his condition remarkably improved with therapy and blood parameters returned normal at the end of 4 weeks and follow up CT revealed no abnormal findings and symptom free thereafter. Conclusion: Acute pancreatitis is usually a sterile inflammatory process caused by chemical autodigestion of pancreas. The edematous form of acute pancreatitis needs to correct its etiological factor to avoid recurrence. It is observed as an initial manifestation of group A beta hemolytic streptococcal infection in this patient and antibiotics play a role as curative and prophylactic in selected cases.